ANALISIS MINAT BELAJAR SISWA SMP PADA PEMBELAJARAN MATEMATIKA - Asih Asih; Adi Ihsan Imami (IKIP Siliwangi, 2021)
The purpose of this research is to analyze interest in Junior High School students of learning in mathematics subject. In this research using qualitative approach with descriptive method, and the population is student in one of Junior High School in Bekasi. Sample in this research is 22 students. Non tes instrument or questionnaire using in this research with 18 item of statement that cover positive and negative statement. This instrument is made of 4 indicator of interest in mathematics subject. The data analysis technique used in this reserach is to use the formula dor the percentage of students’ answers which are then described using the criteria for interpreting the results of students’ answers. The result is obtained from analyze this research that show interest of learn mathematic subject in feeling happier in attend mathematics subject, having interest in attend every mathematic study hours, and has discipline attitude in studying mathematics that shows most of the student having interest in studying mathematics. And for indicator more attention and specific in learn mathematis, most of student give more attention for mathematic subject. In general percentage of average in questionnaire data shows that 72,25% it means mainly student in Junior High School in Bekasi have interest in mathematics subject.